Contraceptive knowledge among women at risk of unintended pregnancy in Kingston, Jamaica. Issue 3 (16th March 2021) - Hylton-Kong, Tina; Bailey, Althea; Steiner, Markus J.; Gallo, Maria F.
ABSTRACT: Low contraceptive knowledge may limit contraception initiation or continuation and, consequently, could represent an important, modifiable cause of unintended pregnancy. The objective of this analysis was to identify correlates of knowledge among women at risk of unintended pregnancy. We analyzed data from a study of 222 young women attending a public clinic in Kingston in November 2018 to March 2019. We measured contraceptive knowledge with seven questions on method reversibility, ability to use covertly, contraindications, and side effects. We used multivariable linear regression to evaluate the correlates of summary knowledge scores and report beta coefficients, which represent differences in mean summary knowledge scores. The mean knowledge score was low (2.7; range = 0–7). Only 30.2% of the participants correctly identified intrauterine devices as more effective than oral contraception, male condoms, and withdrawal. Women who reported that their provider discussed contraception scored higher (adjusted ß = 0.37, p = 0.05) than those not reporting this. Women who perceived implants as very/mostly safe scored higher (adjusted ß = 0.45, p = 0.01) than those perceiving the device as mostly/very unsafe. Finally, compared to contraception non-users, women using less-effective contraception had a lower score (adjusted ß = −0.40, p = 0.04) while those using effective contraception did not differ in scores (ß = −0.30, p = 0.18). Overall, we found poor contraceptive knowledge among young women in Kingston. Providers appeared to hold an important role in women's understanding of contraception.